Polri Performance: The Relationship to Achievement Motivation and The Working Environment - Hari Slamet Trianto; Christiana Hari Soetjiningsih; Adi Setiawan (PSIKODIMENSIA, 2020)
The purpose of this study is examining the effect of achievement motivation and work environment simultaneously on the performance of Police Officers. This research is a type of quantitative research. The participants in this study were 100 police officers in Salatiga with saturation sampling technique. The instrument used was Achievement Motivation Scale, Work Environtment Scale, and Performance Scale.Data analysis technique used multiple liniar regression. The results showed that achievement motivation and work environment proved to simultaneously have a significant effect on the performance of police officers with contribution value of 28.50%. This shows that the higher the achievement motivation and the better the work environment, the higher of performance of Police Officers. Achievement motivation and work environment as predictor the performance of police officers.